Hindu-Muslim religious encounter in Bangladesh: a case study in Dhaka - Rahman, Md. Asadur; Ali, Md. Yousuf; Mohamed Zein, Ibrahim (IIUM Press, 2017)
This study investigates the present condition of Hindu-Muslim relations in Bangladesh, a multi religious country in South Asia with Muslim majority. It is based on in-depth interview with 18 Hindu and 18 Muslim respondnets in Dhaka, the capital city. Among these 18 from each category, the type of the respondents the booker has selected is religious scholars, cultural activists, and educationists cum community representatives. The study aims to justify the propagations and sense of Hindu-Muslim confrontation as reflected in many narratives and literatures where an attempt to portray the felt absence of interreligious harmony.